PFC Control for LED Lamp Driver Using Sensorless Predictive Current Controller - Zaky, M. S.; Azazi, H. Z.; Touti, E. (Engineering, Technology & Applied Science Research, 2018)
Light-emitting diodes (LEDs) have recently become of utmost significance to replace conventional lighting sources. Power factor correction (PFC) control of LED lamps requires three sensors which cause more cost, increase time delay, and increase noise, thus reducing drive reliability. Alternative methods to estimate the inductor current instead of its measurement are mandatory. This paper proposes a sensorless predictive current controller to enhance power factor (PF) of LED lamp driver and reduce driver cost. The inductor current is estimated instead of employing current sensor relying on measured input and output voltages. Zero-crossing detector is utilized to accomplish robust performance during distorted supply voltage. The controller and power circuit are isolated. The control algorithm employs a two-loop control to achieve a high PF with sinusoidal input current. Rapid speed performance is accomplished. The influences of PFC on input current value, PF and harmonic orders are presented. A prototype LED lamp driver with the suggested PFC structure is tested practically by a digital signal processor (DSP) DS1104 platform to validate its effectiveness. Experimental tests under various working conditions are provided to prove the usefulness of the suggested PFC control.